UPAYA PENINGKATAN KESADARAN MASYARAKAT TERHADAP PENCEGAHAN COVID-19 DI WILAYAH KELURAHAN BABAKAN - Dina Dina; Rita Sri Rahayu; Rekha Sity Nurlatifah; Iwan Maulana; Riandy Hidayat; Hanipah Inan Nuraeni; Sugi Prayoga; Veriana Wijoyo; Arie Kresnawan (Jurnal Pengabdian Kepada Masyarakat Babakti, 2022)
The Covid-19 pandemic that is endemic in Indonesia has become a national problem for the past two years. The government's efforts to suppress the spread of Covid-19 are not in line with community support. The Real Work Lecture Program (KKN) for Al-Ghifari University Students which was held in Babakan Village, Babakan Ciparay District, Bandung aimed to provide education and socialization regarding raising awareness as an effort to prevent Covid-19. The activity stages include observations made by the author regarding the condition of the community and interviews with local officials. The Work Program was implemented according to procedures and went well, and received a positive response. This is shown by increasing public understanding and awareness about the dangers of Covid-19, by starting to carry out health procedures, washing hands, wearing masks, avoiding crowds, as well as the importance of vaccination with the large number of people who will be vaccinated.